2010
DOI: 10.1111/j.1475-097x.2010.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery after constant-load exercise tests is decreased in proportion to the importance (severity and diffusion) of exercise-induced lower-limb ischaemia

Abstract: During constant-load treadmill testing, DROPtot, an index of the 'importance' of exercise-induced lower-limb ischaemia, correlates with HRR1. Whether HRR1 is improved in proportion of DROPtot improvement in patients undergoing surgery or rehabilitation for peripheral artery disease is a fascinating issue for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This is consistent with our first hypothesis, i.e., that low PaO 2 level may delay post-exercise HRR (Ba et al, 2009; Mahe et al, 2011). There was however no clear correlation between HRR 60s and PaO 2 level (Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with our first hypothesis, i.e., that low PaO 2 level may delay post-exercise HRR (Ba et al, 2009; Mahe et al, 2011). There was however no clear correlation between HRR 60s and PaO 2 level (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…Differences in exercise intensity (supramaximal vs. maximal or submaximal) can also explain these discrepancies. The supramaximal exercise used in the present study (i.e., all-out 20-s sprint) was likely to elicit a greater anaerobic glycolytic participation than a constant submaximal (present Sub data and those from Mahe et al (2011)) and/or incremental exercise (eliciting 90% of subjects’ maximal HR; Ba et al, 2009). Compared with these latter lower-intensity exercises, the greater metabolite accumulation in the blood observed after Supra was likely associated with an almost-maximal autonomic activity perturbation (Buchheit et al, 2007a); the superimposed hypoxic stimulation was therefore unlikely to further impair cardiac autonomic activity (Figure 4).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Previous studies have observed a higher rate of acute cardiovascular events(38) and a greater prevalence of hospitalization associated with vascular procedures(11) in men. Moreover, a recent study also observed that after constant load treadmill walking, men with PAD presented a slower HR recovery than women(24). Taking together, the available evidence suggests a worse cardiovascular control in men with PAD, which might be related to the greater cardiovascular responses during the constant load walking.…”
Section: Discussionmentioning
confidence: 91%